1992
DOI: 10.4315/0362-028x-55.11.902
|View full text |Cite
|
Sign up to set email alerts
|

Migration of Patulin in Apples

Abstract: The migration of patulin in apples was studied. A patulin-producing Penicillium expansum strain, isolated from apples, was inoculated in sound apples. Patulin was extracted and its migration was studied in each centimeter from the point of inoculation. Trimming just the rotten tissue was not enough to exclude all patulin. At 1 cm from the periphery of the rotten area, no patulin could be detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 0 publications
0
32
0
Order By: Relevance
“…A patulin-producing Penicillium expansum strain, isolated from apples, was inoculated in sound apples and migration of patulin from the point of inoculation was studied (121). Trimming just the rotten tissue was not enough to exclude all patulin, but removal of 1 cm around the rotten tissue would be satisfactory, the toxin not being detected at this distance.…”
Section: Prevention Control and Effects Of Processingmentioning
confidence: 99%
“…A patulin-producing Penicillium expansum strain, isolated from apples, was inoculated in sound apples and migration of patulin from the point of inoculation was studied (121). Trimming just the rotten tissue was not enough to exclude all patulin, but removal of 1 cm around the rotten tissue would be satisfactory, the toxin not being detected at this distance.…”
Section: Prevention Control and Effects Of Processingmentioning
confidence: 99%
“…Furthermore, patulin can be detected in visibly sound fruit [206] and can spread from rotten areas of apples into sound areas [220]. Two studies have shown that patulin could diffuse 1 to 2 cm from the rotten core in apples [217,221]. Producers' tests on apples have shown that the patulin level is often not related to the physical quality of the fruit, with both high-rot fruit and top-quality eating fruit often having high levels of patulin [48].…”
Section: During Juice Production: Preparation For Crushing Filteringmentioning
confidence: 99%
“…As previously mentioned, processed apple products are often made from lower quality fruit that is unsuitable for direct market retail. Removal of decayed/damaged fruit or trimming of moldy portions can significantly reduce patulin levels in apple products [216][217][218][219][220]. Trimming of rotten sections of apple has been shown to remove up to 99% of patulin contamination [209].…”
Section: During Juice Production: Preparation For Crushing Filteringmentioning
confidence: 99%
“…Even accepting batches for juice production with the lowest possible amount of damaged apple creates a high risk of contamination for healthy fruit. Moreover, it was reported that cleaning procedures and elimination of rotten tissue before pressing do not necessarily eliminate completely all the patulin present, as this toxin is highly soluble in water and diffuses to healthy tissue [37]. As we report, the presence of patulinproducing Penicillium spp.…”
Section: Discussionmentioning
confidence: 56%